Modificación de la Ley del Artista Intérprete y Ejecutante y la contratación laboral del menor de 12 años en Perú - Espejo Vargas, Zuliana Del Carmen (2023)
The present thesis report called: "Modification of the Law of the Artist, Interpreter and Performer and the labor contracting of minors under 12 years of age in Peru", was carried out with the objective of analyzing the need to modify the labor legislation of the minor artist. 12 years old, an increasingly pressing and little-treated social reality in Peru. The methodology includes the documentary analysis of the bibliographic sources obtained from the doctrinal current, scientific articles, national legislation, as well as the comparative one, and the analysis of the jurisprudence on cases referring to the subject. The problem referred to the lack of legal protection of minors who work as artists was addressed; Likewise, data was obtained through a survey of law operators. It was concluded that there is a legal vacuum in the regulations analyzed, that it is necessary to modify the Law of the Artist, Interpreter and Performer because it would contribute to the modernization of labor legislation and compliance with the best interest of the child artist. It was recommended that the legislators prepare a Bill with the modification of the norm that protects minors who work as artists.